(3GdhGaj HGdhajGJs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3ef UGYO Hf GdMSf GdOeTbi s
(3BNQgG (B:s
(3Edi YHOGddg Hf MPGbI s
(3fSNI djSJ cGedIs
(3hYdi HYV CLRGFgG JhbjY GHf ObeGb HGdeWGdYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B32 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B283 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs